Cyber-Ostracism, Depression, and Adolescents’ Cyberbullying Perpetration: A Cross-Lagged Panel Analysis - Ding, Huimin; Zhao, Chengjia; Huang, Feng; Zhu, Liyue; Wei, Hua; Lei, Li (Youth & society, 2025)
This study explores the complex dynamics between cyber-ostracism, depression, and cyberbullying among 870 Chinese adolescents (50.9% boys, Mage = 13.03, SD = 0.76). Using a cross-lagged panel analysis, the results found: (1) bidirectional associations between cyber-ostracism and depression, with cyber-ostracism at Time 1(T1) significantly and positively predicted depression at Time 2(T2), and depression at T1 significantly and positively predicted cyber-ostracism at T2; (2) depression at T1 significantly and positively predicted cyberbullying perpetration at T2; (3) cyberbullying perpetration at T1 significantly and positively predicted cyber-ostracism at T2; (4) depression mediated the relationship between cyber-ostracism and cyberbullying perpetration, and (5) gender differences were observed only in the path from depression at T1 to cyber-ostracism at T2, with a significant association for girls but not for boys. This study highlights the complex interplay between cyber-ostracism, depression, and adolescents’ cyberbullying perpetration, shedding light on the importance of addressing these issues in a gender-sensitive manner.